The Influence of Job Description and Work Discipline on Employee Performance at Public Fuel Station CV Berkah Arofah in Malang - Hammad Akram; Praptini Yulianti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to determine and analyze the influence of job description and work discipline variables on employee performance at Public Fuel Station (SPBU) CV. Berkah Arofah Malang. The analysis used in this study is descriptive and quantitative, with primary data obtained directly through a questionnaire distributed to all respondents, taken from the employees of CV Berkah Arofah. The population in the study is 31 respondents; the data collection technique uses a saturated sample that uses the entire population within the study as a sample. In this research, the validity and reliability of data were tested to ensure data accuracy and consistency. The measurement scale in this study uses a Likert scale 1-5. Data analysis was carried out using SPSS Statistics 18 for Windows. The findings suggest that while job descriptions do not significantly influence employee performance, work discipline has a strong positive effect. The study concludes that adherence to work discipline is crucial for enhancing employee performance within the organization.